P1003STUDY DESIGN OF THE ROTATION FOR OPTIMAL TARGETING OF ALBUMINURIA AND TREATMENT EVALUATION (ROTATE-3): A ROTATION STUDY OF DIFFERENT ALBUMINURIA LOWERING DRUGS CLASSES TO STUDY INDIVIDUAL DRUG RESPONSE IN DIABETIC AND NON-DIABETIC CKD. (6th June 2020) - Provenzano, Michele; Puchades Montesa, Maria Jesãºs; De Nicola, Luca; D'Marco, Luis; Garofalo, Carlo; Sasso, Ferdinando Carlo; Acierno, Carlo; Panizo Gonzalez, Nayara; Romero-Parra, Maria; Sen, Taha; Gagliardi, Ida; Hoyo-Garcia, Rafael; et al.
Abstract: Background and Aims: Patients with diabetic kidney disease show a wide variability in their response to established and new treatments. SGLT2 inhibitors have also shown to slow the progression of kidney disease. Some studies have also shown kidney benefits for Mineralocorticoid Receptor Antagonists (MRA). A large outcome trial with the MRA finerenone is currently ongoing to assess effects of this MRA on major kidney outcomes. The individual trials will solve the issue whether a patient may have benefit from an SGLT2 inhibitor or MRA, but they do not address the key question which of the two or their combination is better to reduce albuminuria for each individual patient. Therefore, we designed the ROTATE-3 trial is designed to investigate the individual albuminuria response to MRA (eplerenone), SGLT2 inhibitor (dapagliflozin) or the combination. Method: ROTATE-3 is a randomized, prospective, open label, multicentre, crossover trial with a total duration of 28 (to 42) weeks [EudraCT number: 2017-004641-25]. Patients with or without type 2 diabetes, ≥18 years and elevated albuminuria (100-3500 mg/24 hour) already receiving a stable (same dose at least 4 weeks) maximum tolerated dose of an ACE-inhibitor or Angiotensin Receptor Blocker will be enrolled.Patients receive in random order 4 weeks of treatment with the eplerenone 50 mg/day, dapagliflozin 10 mg/day or combination of both drugs with a 4-weeks wash-out period in between. After the last treatment period patients will proceed to a 4-weeks wash-out period. The primary study outcome is the correlation in albuminuria response to eplerenone and dapagliflozin for which 46 patients provides 80% power to detect a Pearson correlation coefficient of 0.4 between the log transformed albuminuria response to eplerenone and dapagliflozin. Blood is collected for clinical chemistry every two weeks during each treatment period. Patients are requested to collect one 24-hour urine sample at start and at end of each treatment period. Home blood pressure is monitored every 2 days. Results: As of January 1 st 2020 the study has enrolled 13 patients. It is anticipated that recruitment will be completed by December 2020 with study completion in August 2021. Conclusion: The results of the ROTATE-3 study will provide more insight in the individual albuminuria lowering response to potentially two new treatment options for patients with CKD and may help to implement personalized medicine in diabetic kidney disease.Study sponsored by University Medical Center Groningen. The Netherlands.